2014
DOI: 10.2478/ppb-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of Conscientiousness: The Antagonistic Interests among Obsessive and Antisocial Personalities

Abstract: The five factor trait of conscientiousness is a supertrait, denoting on one hand a pattern of excessive labor, rigidity, orderliness and compulsivity, and on the other hand a pattern of strict rectitude, scrupulosity, dutifulness and morality. In both respects the obsessive-compulsive personality is conscientious; indeed, it has been labeled a disorder of extreme conscientiousness (Widiger et al., 2009). Antisocial personality disorder, in the present paper, is described as occupying the opposite end of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 66 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Mealey's (1995) antisocial, then, is a coherent behavioral package in that multiple traits strategically covary in service of a particular adaptive end. Though antisocial and obsessive strategies are in almost every respect opposite (Hertler, 2014b), both might have been shaped into coherent behavioral packages by evolutionary pressures (Hertler, 2014b). Just as the antisocial combined restricted anxiety, empathy and guilt with high sensation seeking, impulsivity and roving behavior to exploit honest population members, so the obsessive combined anxious tension, future oriented thought and conscientiousness with low sensation seeking, compulsivity and routinized behavior to cope with predictably harsh seasonality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mealey's (1995) antisocial, then, is a coherent behavioral package in that multiple traits strategically covary in service of a particular adaptive end. Though antisocial and obsessive strategies are in almost every respect opposite (Hertler, 2014b), both might have been shaped into coherent behavioral packages by evolutionary pressures (Hertler, 2014b). Just as the antisocial combined restricted anxiety, empathy and guilt with high sensation seeking, impulsivity and roving behavior to exploit honest population members, so the obsessive combined anxious tension, future oriented thought and conscientiousness with low sensation seeking, compulsivity and routinized behavior to cope with predictably harsh seasonality.…”
Section: Discussionmentioning
confidence: 99%
“…It was alternatively suggested that an evolutionary model could most parsimoniously explain the existence of obsessive personality and its perpetuation from one generation to the next (Hertler, 2014a). Subsequently, such an evolutionary model was briefly sketched (Hertler, 2014b) and thereafter treated at length (Hertler, 2015a). In this latter work, obsessive character was described as a non-conditional, heritable behavioral complex, evolving during the Upper Paleolithic and Early Neolithic in response to changing selective pressures that came of northerly migration out of Africa.…”
Section: The Purpose and Structure Of The Present Articlementioning
confidence: 99%
See 3 more Smart Citations